Successful Microsurgical Reconstruction for Limb Salvage in a COVID-19-Positive Patient: A Case Report - Fleury, Christopher M.; Chang, Brian L.; Slamin, Robert P.; Schwitzer, Jonathan A.; Kanuri, Arjun; Masden, Derek L. (Journal of Reconstructive Microsurgery Open, 2021)
Background Although the novel 2019 coronavirus (COVID-19) pandemic delayed elective microsurgical reconstruction cases, traumatic injuries requiring microsurgical reconstruction for limb salvage still presented to our hospital. Recent data suggests a link between COVID-19 and increased venous and arterial thromboembolic events, theoretically increasing the risk of microvascular anastomotic thrombosis and flap failure.Methods We provide a single case report of microsurgical limb salvage in a COVID-19-positive patient with a Gustilo IIIb open tibial-fibular fracture.Results A free latissimus dorsi muscle flap was used to successfully cover a Gustilo IIIb open tibial-fibular fracture with exposed orthopedic hardware and large soft tissue defect, with 5-month follow-up demonstrating a well-healed flap allowing for preserved ambulation.Conclusion Although there is a theoretical increased incidence of venous and arterial thrombotic microvascular failure in COVID-19-positive patients, microsurgical reconstruction is occasionally the lone option for salvage. Microsurgical reconstruction in this population must be carefully considered, meticulously executed, and closely monitored.
Keywords: microsurgery; COVID-19; limb salvage